Anterior temporal face patches: a meta-analysis and empirical study - Von Der Heide, Rebecca J.; Skipper, Laura M.; Olson, Ingrid R. (Frontiers in Human Neuroscience, 2013)
Studies of nonhuman primates have reported face sensitive patches in the ventral anterior temporal lobes (ATL). In humans, ATL resection or damage causes an associative prosopagnosia in which face perception is intact but face memory is compromised. Some fMRI studies have extended these findings using famous and familiar faces. However, it is unclear whether these regions in the human ATL are in locations comparable to those reported in non-human primates, typically using unfamiliar faces. We present the results of two studies of person memory: a meta-analysis of existing fMRI studies and an empirical fMRI study using optimized imaging parameters. Both studies showed left-lateralized ATL activations to familiar individuals while novel faces activated the right ATL. Activations to famous faces were quite ventral, similar to what has been reported in monkeys. These findings suggest that face memory-sensitive patches in the human ATL are in the ventral/polar ATL.